Analysis of Students' Computational Thinking Ability in Solving Contextual Problems - Muh Hanif Abidi; Hendarto Cahyono; Reni Dwi Susanti (Department of Mathematics Education University of Muhammadiyah Malang, 2023)
This study aims to examine students' computational thinking skills in solving contextual problems in the matter of a system of two-variable linear equations. This type of research uses descriptive qualitative approach. The subjects used in this study were 25 class VIII students of State Middle School in the 2022/2023 academic year on SPLDV material (System of Two-Variable Linear Equations). Data collection techniques and instruments in this study were written tests and interviews. Data analysis was carried out by first classifying the data, then presenting the data and ending by concluding the results of computational thinking indicators. The results showed that the percentage of students' computational thinking aspects, namely the decomposition aspect, was 70.30% in the good category, pattern recognition 58.63% sufficient category, abstraction 58.30% sufficient category, and thinking algorithm 50.47% sufficient category. So that students' computational thinking skills are included in the sufficient category. Meanwhile, based on the categorization of high-level students they have done well. However, there were several steps that were missed and not written down in the answer sheets, such as the decomposition and pattern recognition aspects which were not carried out properly. For the medium category, all stages of computational thinking have been carried out very well starting from decomposition, pattern recognition, abstraction, and thinking algorithms. For the low category, this category has not been able to carry out the stages of computational thinking properly.